A review of food reformulation of baked products to reduce added sugar intake. (April 2019) - Luo, Xiao; Arcot, Jayashree; Gill, Timothy; Louie, Jimmy C.Y.; Rangan, Anna
Abstract: Background: Excessive consumption of added sugar is negatively associated with many health outcomes. Cakes and biscuits are popular discretionary foods that contribute significant amounts of added sugar to people's diets. Food reformulation may allow an efficient reduction in dietary sugar at a population level without shifting the individual's dietary pattern. Scope and approach: The aim of this review was to examine the literature on reformulation of baked products to reduce added sugar. Sucrose plays multiple vital roles in baked products, such as sweetness and bulking, and suitable substitutes must be able to address these functions. A range of potential sucrose substitutes are discussed. Key findings and conclusions: Polyols provide both bulk and sweetness though less than sucrose. Non-nutritive sweeteners (NNS) are commonly used in combination with polyols and bulking agents. Stevia, though with a noticeable metallic aftertaste, is the most studied NNS in baked products. Acesulfame-K, sucralose and encapsulated aspartame are also able to replace sucrose with low-calorie carbohydrates (oligofructose, maltodextrin and polydextrose) or polyols. This review indicates that maltitol seems the most suitable sole sucrose substitute at present, while diverse mixtures of NNS, polyols and low-calorie carbohydrates can also deliver the functionalities of sucrose in baked products. Highlights: Cakes and biscuits contribute high amounts of added sugar intake worldwide, and food reformulation is effective to reduce added sugar intake. Very limited quantity of sucrose can be reduced from cakes and biscuits without replacing sucrose with suitable alternatives. Non-nutritive sweeteners, polyols and low-calorie carbohydrates in baked products are reviewed as potential alternatives to sucrose Commercially reformulated low/no added sugar baked products are reviewed. The currently most feasible options for reformulation of sugar reduced cakes and biscuits are presented.